DIGITALIZATION FOR ENVIRONMENTAL SUSTAINABILITY: EVIDENCE FROM THE ICT–CARBON EMISSIONS NEXUS IN SUB-SAHARAN AFRICA - Ebrima Khan; Taridi Kasbi Ridho; Lamin Panneh; Modou Secka; Saikou Darboe (Universitas Sebelas Maret (UNS), 2026)
The rapid expansion of digitalization across Sub-Saharan Africa has created new opportunities for economic development, yet its impact on environmental sustainability remains unclear. This study investigates the relationship between digitalization and environmental quality in 41 countries in Sub-Saharan Africa over the period 2004–2023. Digitalisation is measured through internet usage, mobile subscriptions, and a composite ICT index, while carbon dioxide (CO₂) emissions serve as the indicator of environmental quality. Prior to estimation, a collection of diagnostic tests was conducted to ensure methodological rigour and guide model selection. Employing a dynamic two-way fixed effects framework that accounts for both country-specific and time-specific effects, the findings indicate that digitalization contributes to improved environmental quality through reductions in CO₂ emissions. Renewable energy consumption is also found to mitigate environmental degradation, whereas economic growth, trade openness, and foreign direct investment tend to increase emissions. Notably, the Dumitrescu–Hurlin panel Granger causality test confirms a bidirectional causal relationship between ICT and CO₂ emissions, suggesting a feedback mechanism between digitalisation and environmental outcomes. Overall, the findings suggest that digitalization can support environmental sustainability in Sub-Saharan Africa when complemented by renewable energy expansion and appropriate environmental policies. The study provides policy recommendations for promoting environmentally sustainable digital transformation in Sub-Saharan Africa.